Emergence of Vancomycin Intermediate Staphylococcus aureus (VISA) in a Tertiary Care Hospital in Lahore: An Alarming Situation - Arshad, Faiqa; Javed, Iffat; Mushtaq, Sohaila; Anwer, Saeed (International Journal of Pathology, 2018)
Objectives: To assess the current situation of vancomycin MIC values and to find out the possible presence ofvancomycin intermediate or resistant Staphylococcus aureus strains in a tertiary care hospital of Lahore, Pakistan.Study Design: Non-interventional, descriptive study.Place and Duration of Study: Pathology Department, Post Graduate Medical Institute, Lahore from February 2013to October 2013.Methodology: A total of 50 consecutive isolates of methicillin resistant Staphylococcus aureus (MRSA) wereidentified by using cefoxitin disc diffusion test. The confirmation of methicillin resistance was done by PBP2alatex agglutination test. E-test strips (AB Biodisk, Biomeurix) were used for the determination of VancomycinMIC values for MRSA strains and results were interpreted according to clinical and laboratory standards institute(CLSI) guidelines.Results: Result of our study showed that the range of MIC values of vancomycin for MRSA was 1.5-4 ug/ml.Among a total of 50 MRSA isolates, four strains (8%) were identified as vancomycin intermediate Staphylococcusaureus (VISA) with MIC value of 4μg/ml. Mean vancomycin MIC value was 2.5ug/ml whereas MIC50 andMIC90 values of vancomycin were 2ug/ml and 3ug/ml respectively.Conclusion: The emergence of vancomycin Intermediate Staphylococcus aureus in our setup is an alarmingsituation. The widespread use of vancomycin for the treatment of MRSA might have induced a selection pressure,thus resulted in the emergence of these notorious resistance strains. Our study accentuates the need forcontinuous monitoring of vancomycin MIC levels in MRSA infections. A strict regulation on irrational antibioticusages might be an effective approach in this direction. Proper infection control policies must be adopted toprevent the transmission of resistance strains.